Deconstructing the Female Antagonist of the Coronation Scandal in B's Vita Dunstani. Issue 4 (19th May 2022) - Firth, Matthew
ABSTRACT: The clerical author known as B provides the earliest account of one of pre-Conquest England's more infamous tales: the coronation scandal of 955. In his Vita S. Dunstani, written 995 × 1005, B recounts that King Eadwig (955–959) absconded from his coronation feast, later to be found by Dunstan, the Abbot of Glastonbury, engaging in a sexual liaison with two women, a mother and daughter. Dunstan's forcible separation of Eadwig from the two women is presented as the genesis for a feud that plays out between Dunstan and the older of the two women, Æthelgifu. Where much previous analysis of this episode has focused on the saint, Dunstan, and the king, Eadwig, this article seeks to centre Æthelgifu as the primary antagonist of the story. In so doing, it undertakes a detailed examination of her character construct, considering the political situation, intertextual models and biblical archetypes that inform it.